Efecto de los niveles de urea sobre la fermentación anaeróbica y las características bromatológicas de la pulpa de banano (Musa spp.) - Litardo Palomino, Teófilo Johan (2024)
Bananas, a fruit with high nutritional value, are an underutilized byproduct, with Ecuador being one of the main banana exporters in Latin America. There are large quantities of rejection due to not meeting industry standards, which can be reused as animal feed, offering a profitable alternative to reduce inputs and provide a diet during times of scarcity. This study focuses on analyzing the effect of urea on the anaerobic fermentation of banana pulp, seeking to increase its protein value. The research was based on a completely randomized experimental design with a 3x3 bifactorial arrangement, with days of fermentation and urea levels. 19 samples of banana pulp packaged in microsilos were used. Bromatological techniques were used. The analyzes of moisture, protein, ether extract, ash, fiber and non-nitrogen components revealed that both urea levels and days of fermentation significantly influence various nutritional characteristics. The evaluation of two levels of urea over periods of days of fermentation revealed its significant impact on several silage quality parameters. The economic analysis of the treatments allowed evaluating the economic viability of different levels of urea in pulp fermentation, providing a practical perspective for producers. These results provide a solid basis for making informed decisions about pulp production and processing. This research can guide future studies on optimal use of banana pulp as a food resource.